Why have corporate tax revenues declined?: Another look - Alan J. Auerbach (Center for Economic Studies and ifo Institute (CESifo), 2006)
The relative constancy of nonfinancial corporate tax revenues as a share of U.S. GDP masks offsetting trends in the ratio of corporate profits to GDP (declining) and the average tax rate (increasing). The average tax rate rose steadily between 1996 and 2003, an increase largely attributable to the importance of tax losses. This rise casts some doubt on the role of tax planning activities in reducing corporate taxes. So, too, does the relative stability of the rate of profit (relative to net assets), which might be expected to have declined had the understatement of profits for tax purposes been increasing.
Keywords: H25; G32; 330; Körperschaftsteuer; Industrie; Steueraufkommen; USA